2008
DOI: 10.1016/j.hrthm.2007.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transient dynamics and the mechanisms of ventricular vulnerability to single premature electrical stimulation in Langendorff-perfused rabbit ventricles

Abstract: We conclude that a strong premature stimulus can induce a Ca(i) sinkhole at the entrance of the CCP. Spontaneous Ca(i) elevation in the Ca(i) sinkhole precedes the V(m) depolarization, leading to Ca current-mediated slow propagation in the CCP. The slow propagation allows more time for tissues at the other side of CCP to recover and be excited to complete figure-eight reentry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Hearts were stimulated using a ramp pacing protocol [ 42 , 47 ] starting from the basic cycle length (CL) of 350 ms to shorter CL with 10-ms steps until either loss of 1:1 capture or VF induction. Ryanodine (2 μM) was perfused for 30 minutes, and the standard stimulation protocol was repeated.…”
Section: Methodsmentioning
confidence: 99%
“…Hearts were stimulated using a ramp pacing protocol [ 42 , 47 ] starting from the basic cycle length (CL) of 350 ms to shorter CL with 10-ms steps until either loss of 1:1 capture or VF induction. Ryanodine (2 μM) was perfused for 30 minutes, and the standard stimulation protocol was repeated.…”
Section: Methodsmentioning
confidence: 99%
“…The method has been used to track the sequences of electrical activation and force generation as well as cardiac repolarization and relaxation as a function of rate and sympathetic activity and during electrically induced ventricular fibrillation (VF) and defibrillation. Dual optical mapping has been playing an important role in elucidating arrhythmia mechanisms in models of heart failure (London et al, ), long QT syndrome (Choi et al, ), and ischemia/reperfusion (Choi and Salama, ; Lakireddy et al, ; Choi et al, ,b; Lakireddy et al, ), and in genetically altered animal models of human cardiac diseases (Katra et al, ; Katra and Laurita, ; Lan et al, ; London et al, ; Roell et al, ; Hayashi et al, ; Laurita and Rosenbaum, ; Saba et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the present study, it is reasonable to hypothesize that these postshock virtual electrodes can cause differential Ca i transients, with virtual anode sites generating larger Ca i transients than at the virtual cathode sites. 13, 27 Hwang et al 8 subsequently confirmed that there is postshock Ca i heterogeneity after near-threshold defibrillation shocks. The first beat of postshock activation always occurs from the Ca i sinkhole.…”
Section: Discussionmentioning
confidence: 94%